RANCANGAN STRATEGI PENGEMBANGAN USAHA DENGAN PENDEKATAN BLUE OCEAN STRATEGY PADA USAHA BAKSO HADIRIN KENCONG KABUPATEN JEMBER - Sari, Nur Ita; Sari, Maheni Ika; Rahayu, Jekti (Relawan Jurnal Indonesia, 2022)
Bakso Hadirin is an SME engaged in the culinary industry in general meatballs are served with hot and clear soup, but the father hadirin as the founder and owner of the Bakso Hadirin made a new innovation to produce pentol in frozen food packaging therefore bakso hadirin need to design the right strategy to compete and develop the business. Blue Ocean Strategy is a strategy that the company applies together with its tools and frameworks, to be able to create value innovations, where the company is able to create new value for customers, and is able to create a new market space where there are no competitors in it the goal to be achieved in this study, namely to know the analysis of the business development strategy design using the Blue Ocean Strategy (BOS) approach method in the bakso hadirin business Kencong, Jember Regency. The research method uses a qualitative research approach. by using the four-step framework tool and the abolish-reduce-enhance-create scheme. The result of this study is the promotion factor, the product quality factor must be improved, the product factor must be created, the price factor must be consistent, but The bakso hadirin must be able to be consistent in carrying out a promotion so that the products offered can be known by many people and can increase sales in the long term.